Perceived Social Support and Work-Life Balance Among Women at the Commercial Banks in Bangladesh : The Moderating Impact of Work-Life Policies - Mahi Uddin (Universiti Sains Islam Malaysia, 2024)
Perceived social support is a critical resource for individuals for a greater work-life balance. Although perceived social support and work-life balance have widely attracted the attention of both academics and practitioners, the link between these two concepts has not been widely studied yet in literature, especially in banking service sector in developing country perspective. Additionally, there is contradictory evidence on which perceived social support sources facilitate work-life balance. Thus, this study examines the impact of perceived social support sources on work-life balance in the banking industry, in order to examine which perceived social support sources facilitate work-life balance. Based on the extensive review of the literature on perceived social support and work-life balance, valid and reliable definitions were formulated for both concepts, and then, a conceptual framework was developed to investigate the links between the research variables of interest. Specifically, on this study, data was obtained from female bank employees employed in the 39 commercial banks located in Dhaka and Chittagong in order to test the impact of perceived social support sources on work-life balance. A total of 588 responses were collected employing purposive sampling technique. 29 incomplete questionnaires were eliminated, leaving 559 useable responses and yielding a response rate of 91%. Data were analyzed using descriptive statistics, exploratory factor analysis, and multiple regression and hierarchical regression modeling. The results of descriptive analysis indicate that mean scores of all the variables range from 3.26 to 3.94 and reliability scores varied from 0.737 to 0.851 indicating internal consistency of dimensions. The results of exploratory factor analysis provide solid statistical evidence on the multidimensionality of the perceived social support construct in line with previous studies. The multiple regression result affirms that perceived social support sources such as perceived workplace support, perceived supervisory instrumental support, perceived supervisory emotional support, perceived coworker emotional support, and perceived family support directly improve the work-life balance but the perceived coworker instrumental support does not. However, the hierarchical regression result indicates that work-life policies only moderate the relationship between perceived family support and work-life balance but not the relationships between perceived workplace support and work-life balance, perceived supervisory emotional support and work-life balance, perceived supervisory instrumental support and work-life balance, perceived co-worker emotional support and work-life balance, perceived coworker instrumental support and work-life balance. Therefore, these results help bank management to allocate resources to provide necessary social supports that facilitate employee work-life balance as well as to formulate policies to increase the availability of supports for a greater balance. Finally, this study would benefit if the relationships are tested with an alternative data set than cross-sectional ones. This study suffered from a limitation common to survey research.